1999
DOI: 10.1103/physrevlett.83.4558
|View full text |Cite
|
Sign up to set email alerts
|

Double Twist in Helical Polymer “Soft” Crystals

Abstract: In natural and synthetic materials having non-racemic chiral centers, chirality and structural ordering each play a distinct role in the formation of ordered states. Configurational chirality can be extended to morphological chirality when the phase structures possess low liquid crystalline order. In the crystalline states the crystallization process suppresses the chiral helical morphology due to strong ordering interactions. In this Letter, we report the first observation of helical single lamellar crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 15 publications
5
124
0
Order By: Relevance
“…In this regard, the present work gives a first demonstration of mesoscale shape chirality for Te. Relation of shape to molecular scale chirality has been considered in the formation of chiral (twisted) mesoscopic shapes in several material systems [42][43][44] . For inorganic crystals, this has been observed in bulk form, in quartz for instance 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the present work gives a first demonstration of mesoscale shape chirality for Te. Relation of shape to molecular scale chirality has been considered in the formation of chiral (twisted) mesoscopic shapes in several material systems [42][43][44] . For inorganic crystals, this has been observed in bulk form, in quartz for instance 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, various nanophase materials like nanospheres, 1 nanowires, 2,3 nanoribbons, 3,4 helical structures, 5,6 nanotubes, 7-10 nanofibers 11 etc., with regular and specified morphology have attracted considerable attention owing to their different potential applications ranging from molecular electronics, 12 biomedical sciences, [13][14][15] optoelectronics, and memory devices. 16,17 In the field of intrinsically conductive polymers, for instance, polypyrrole, polythiophene, polyaniline (PANI) etc., the PANI is unique because of its relatively facile processability, excellent environmental stability, tunable conductivity switching between insulating and semiconducting materials, easy acid/base doping/dedoping behavior, reversible redox property, 18 and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and coworkers found that polyester liquid crystal with chiral entities can self-assemble into crystalline helical superstructures with micrometer-scale pitch length. [12,13] Also,…”
mentioning
confidence: 98%
“…Mimicking nature, scientists have aimed to prepare helical morphologies from the self-assembly of synthetic molecules. A variety of origins for the formation of helical morphologies, including hydrogen bonds, [3] solvophobic interactions, [4][5][6] p-p interactions, [7][8][9][10][11] cholesteric liquid crystal formation, [12,13] relative incompatibility [14][15][16] and chirality, [17][18][19][20] have been demonstrated.…”
mentioning
confidence: 99%